Aktivitas Antioksidan dan Toksisitas Akut Zat Ekstraktif dari Residu Penyulingan Surian (Toona sinensis Roemor) - Rita K Sari; Desi Melianti; Wasrin Syafii; Dewi R Agungpriyono (Jurnal Ilmu dan Teknologi Kayu Tropis, 2013)
The objective of this research was to determine the yield, antioxidant activity, acute toxicity, and phytochemical compound of extractives from left over distilling liquid and distillation residues of various part of surian (Toona sinensis). The extracts from the left over distilling liquid of leaves, heartwood, and sapwood were assigned as LL, HL, and SL, respectively, whereas LB, HB, and SB were respectively the extracts from leaves, heartwood, and sapwood of boiled solid residue. The yield of LL, LB, SL, HL, SB, and HB were 28.78, 10.18, 2.11, 1.74, 0.92, and 0.81% respectively. Based on antioxidant activity test, the LB, LL, and HL extracts were classified as very active with EC50 of 5.45, 5.70, and 5.91 mg ml-1 respectively. The SL was classified as active (EC50 32.36 mg ml-1), the SB and HB extracts were classified as inactive (EC50 > 100 mg ml-1). Based on acute toxicity test, LB is the best natural antioxidant because it was non toxic material (LD50 47752 mg kg-1 BW), while the LL and HL extracts were clasified as low toxicity with LD50 4518.56 and 1999.86 mg kg-1 BW (body weight). The LB extract contained phenol hydroquinone, flavonoids, and tannins (total phenolic content: 94 mg g-1 GAE).